I>JVESTIGATING THE POZZOLANIC/CEMENTING CHARACTERISTICS OF SUGARCANE BAGASSE ASH - HUSSEIN HASSAN, ASMA ABO ELHAMEED (2014)
Sugarcane bagasse ash (SCBA) is a by-product from the sugar industry after juice extraction, a huge quantity of SCBA is being illegally disposed to the environment behind the sugar mills which is unfriendly and does not agree with the environmental protocols. Utilization of such by-products in concrete production will reduce the cement content, cost and the CO, emission accordingly and will also improve the mechanical properties and durability of concrete. Hence the motivation of this research is essentially economical, ecological and technical in nature. The principal aim of this research was to determine the effectiveness of SCBA as a cement replacement material (CRM) for high performance concrete in comparison to the established pozzolans namely densified silica fume (DSF), fly ash (FA) and microwave incinerated rice husk ash (MIRHA).